A MicroRNA Signature in Pediatric Ulcerative Colitis: Deregulation of the miR-4284/CXCL5 Pathway in the Intestinal Epithelium. Issue 5 (May 2015) - Koukos, Georgios; Polytarchou, Christos; Kaplan, Jess L.; Oikonomopoulos, Angelos; Ziring, David; Hommes, Daniel W.; Wahed, Renaisa; Kokkotou, Efi; Pothoulakis, Charalabos; Winter, Harland S.; Iliopoulos, Dimitrios
Abstract : Background: Twenty to 25% of the patients with inflammatory bowel disease (IBD) present the disease before the age of 18 to 20, with worse extent and severity, compared with adult-onset IBD. We sought to identify the differential expression of microRNAs in pediatric ulcerative colitis (UC) and their association with different clinical phenotypes. Methods: MicroRNA expression analysis was performed in colonic tissues derived from pediatric patients with UC and controls without IBD. MiR-4284 levels were verified by real-time quantitative polymerase chain reaction in 2 additional cohorts of pediatric patients with UC. Bioinformatics analysis was performed to predict the targets of miR-4284. In vitro experiments using luciferase reporter assays and real-time polymerase chain reaction evaluated the direct effect of miR-4284 on CXCL5 mRNA. In vivo experiments were performed in 2 mouse models of experimental colitis. Results: A 24-microRNA signature was identified in colonic tissues derived from pediatric patients with UC. The most downregulated microRNA in the tissue of pediatric patients UC, relative to non-IBD controls, was miR-4284. In situ hybridization revealed that miR-4284 is present in colonic epithelial cells, and its levels correlate with the disease activity. Furthermore, we found that miR-4284 regulates CXCL5 mRNA expression through binding to its 3′UTR. CXCL5 had increased mRNA levels in colonic tissue from pediatric patients with UC and correlated with disease activity. Furthermore, we found an inverse correlation between miR-4284 and CXCL5 levels in the colonic pediatric UC tissues and in 2 mouse models of experimental colitis. Conclusions: Our data reveal a novel microRNA pediatric UC signature and provide evidence that miR-4284 directly regulates CXCL5 and correlates with the disease activity. Abstract : Article first published online 3 March 2015.Supplemental Digital Content is Available in the Text.